Merger Regulation in Eastern and Southern Africa - Angwenyi, Vincent (Munich Intellectual Property Law Center - MIPLC Studies, 2021)
The socio-economic and political characteristics of the Eastern and Southern Africa (ESA) jurisdictions call for a different approach to competition policy. Competition Policy in the ESA context draws one’s mind to three major themes: development, small market economies and regional integration. This is against a backdrop of other socio-economic and political factors that led to the adoption of competition policies in ESA. Through a comparative assessment of merger review in the European Union, the United States, South Africa, the United Kingdom and ESA, this book seeks to reveal whether or not the merger regulation approach in ESA is optimal and to what extent the approach can be optimised.